Promising polymer-assisted extraction of palladium from supported catalysts in supercritical carbon dioxide. Issue 41 (October 2020) - Ruiu, Andrea; Bauer-Siebenlist, Bernhard; Senila, Marin; Jänisch, Thorsten; Foix, Dominique; Seaudeau-Pirouley, Karine; Lacroix-Desmazes, Patrick
Graphical abstract: Highlights: CO2 -soluble Pd-complexing polymers bearing pyridine units have been synthesized. Cloud point curves of the polymers have been determined in dense CO2 . Extraction of Pd from supported catalysts was performed in CO2 at 40 °C and 25 MPa. Strong effect of the Pd oxidation state on extraction in CO2 was reported. 73 % of Pd was extracted from the catalytic support by the complexing polymers. Abstract: Precious metals, in particular palladium (Pd), have a wide range of daily applications, from automotive catalysts to fine chemistry production. Nevertheless, these metals are relatively rare and highly expensive, considering their massive industrial utilization. In the last decades, different recycling methods have been explored. Nowadays, the most applied methods, namely pyro- and/or hydrometallurgy, involve energy-intensive processes and/or the generation of large amounts of effluents to be treated. Thus, the development of a more sustainable recycling process of precious metals is highly desirable. In the present work, we introduce a sustainable process based on the use of a green solvent, supercritical CO2, operated under mild conditions (P = 25 MPa and T = 40 °C). The extraction process is possible thanks to the addition of CO2 -soluble complexing polymers bearing pyridine units. The proposed method leads to the extraction of more than 70 % of Pd from an aluminosilica-supported catalyst.